Hepatitis B and C in usersofthe centerof testingand counseling (CTA) in Fortaleza-Ceará - Araújo, Maria AL; Sales, Ana Amélia R; Diogenes, Maria Albertina R (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: although the notification data do not show the real magnitude, hepatitis B and C are relevant public health problems due to their high prevalencein the population. Objective: analyzing the presence of serologic markers for hepatitis B and C in users of the center of testing and counseling (CTA) inFortaleza-CE, as well as presenting the social-demographic profile, use of the condom, reasons for searching for CTA and the presence of co-infection of thehepatitis B and C with VDRL and HIV. Methods: descriptive research with quantitative approach. The sample was formed by 291 forms from users who wentto CTA, from August through December 2005, to take the serologic testing to Human Immunodeficiency Virus and syphilis, to whom the tests for Hepatitis Band C were offered. The data were organized in charts and analyzed statistically, comparing variables, using the program EPI-INFO 6.0. Results: the findingsshowed higher frequency of people from 19 to 30 years of age (69,1%), women (70,7%) and single (46%). The serologic markers found were: total anti-HBcreagent (30,6%), HBsAg positive (10,8%), Anti-HCV positive (6,3%). It is worth mentioning that the co-infection Aids and hepatitis B represented 18% fromthe total; it may also be verified that the use of condom occurs only sometimes with a fixed partner (76,3%) and non-fixed (86,6%). Moreover 14% acquiredthe Human Papillomavirus (HPV) last year. Conclusion: with the findings, the need to include the testing to hepatitis B and C in the health service routinemust be considered, aiming at the precocious identification and treatment.